MO165CANCER, KIDNEY AND DIET: THE NUTRITIONAL MANAGEMENT IN ONCO-NEPHROLOGICAL PATIENTS. A SINGLE CENTER EXPERIENCE. (29th May 2021) - Bettiga, Arianna; Di Marco, Federico; Fiorio, Francesco; Vago, Riccardo; Capitanio, Umberto; Salonia, Andrea; Montorsi, Francesco; Trevisani, Francesco
Abstract: Background and Aims: Controlled low-normal protein (LNP) diet in CKD patient is effective in controlling the progression of renal impairment. Oncological guidelines explain how a high protein level should be always required in patients (pts) affected by malignancies in order to compensate the cancer derived metabolism and avoid catabolism. But what about the onco-nephrological pts? Aim of our study is to investigate the metabolic impact of a low-normal protein diet in a consecutive cohort of 103 nephrological pts affected or not by urological non-metastatic malignancies. Method: A consecutive cohort of 103 pts was enrolled in the Urological Department at San Raffaele Scientific Institute between 2018-2020. Inclusion criteria were: Age (>18 years old), eGFR (< 90 ml/min/1.73), Malnutritional Screening Tool (MTS<2), Urological Cancer aggressiveness (no metastatic process), Informed consent (signed). We divided the total cohort in 2 matched subgroups; case (CS: onco-nephrological pts with urological malignancies) and control (CT: nephrological pts) with a 2.1 ratio. Each patient underwent an initial nephrological and nutritional evaluation and was subsequently subjected to a conventional CKD LNP-diet (0, 7-1 g/Kg/die: calories: 30-35 kcal per kg body weight/die) for a period of 6 months (+/- 2 moths). The diet was based on the estimated Glomerular Filtration Rate (CKD-EPI 2012 formula), comorbidities, nutritional status and hypermetabolic conditions. LNP-diets were integrated with aproteic food to maintain a relevant amount of high–biological value proteins, especially for oncological and advanced CKD pts. MTS, Body Mass Index (BMI), Phase Angle (PA), Fat Mass percentage (FM%), Fat-Free Mass Index (FFMI), body cell mass index (BCMI), extracellular:intracellular water ratio (ECW/ICW), waist circumference (WC), lab test exams and clinical variables were examined at baseline and after 6 months. Statistical analysis: Kruskal-Wallis rank sum test; Data analysis: R programming language and RStudio integrated development environment. Results: Population divided as follows: average age: 69.8 (+/- 10.3); ♂ : ♀ ratio: 2.4; Hypertension: 57.28%; Diabetes: 19, 41%; CKD classification: 3, 88% stage 2, 87, 37% above stage 3. At time zero no pts were underweight and 51 % were overweight or obese with difference condition of FM percentage (FM % average: 24.3 % ♀ and 18.1 % ♂for CS pts vs 31.6 % ♀ and 18.2 % ♂for CT pts). Only 2.1% of pts had a PA of less than 4°, considered a negative prognostic index (PA average: 5.6° for CS pts vs 5.5° for CT pts) and 6.3 % of pts had a value of cell mass less than 8 kg/m 2 indicative of reduced lean mass (BCMI average: 10.4 kg / m 2 for CS pts vs 11 kg / m 2 for CT pts). An increase in ECW/ICW ratio greater than 1 was more present in CT pts in respect to CS pts (41.6 % vs 22.8 % and ECW/ICW average: 1.01 for CT pts vs 0.93 for CS pts) as well as WC measurement associated with increased cardiovascular risk (WC average: 87 cm ♀ and 99 cm ♂ for CS pts vs 97 cm ♀ and 104 cm ♂ for CT pts). After 6 months of diet, we observed a similar behavior between the CS and the CT cohorts in terms of renal metabolites and eGFR profile. In fact, the 65% of onco-nephrological and the 55% of nephrological pts displayed a significative decrease in urea plasmatic levels (- 27, 76 mg/dl) and eGFR improvement (+ 6, 27 ml/min/1, 73). The nutritional status, as assessed by the MST, was preserved in both groups during the study. In addition, all pts had an improvement in BMI (CS: 2.8 kg/m 2 ; CT :1.3 kg/m 2 ) PA (CS: 2.8°; CT: 1.3°), BCMI (CS: 1.31 kg / m 2 ; CT :0.38 kg / m 2 ) and FFMI (CS; 0.1 ♀ and 0.1 ♂; CT; 2.9 ♀ and 1.1 ♂) and a decrease of WC (CS: - 1.3 cm; CT– 1, 65), FM percentage (CS: 0 %; CT – 2.7) and ECW/ICW (CS: 0.02; CT 0.03). Conclusion: Our study suggests that LNP high calorie diet ameliorates the nephrological scenarios, the metabolic complications, and the nutritional perspective in uro-oncological pts with stage 2-5 CKD. A larger prospective study to validate these results is on-going.